EDUCATION AND SCHOOLING: WHAT’S THE DIFFERENCE? - Richmond, W. Kenneth (McGill Journal of Education / Revue des sciences de l’éducation de McGill, 1974)
In the first place, why bother to look for a distinction between the two terms? Why all this fuss about the use of words which everyone recognizes to be fuzzy, and why pretend to feel concerned if they are commonly taken to be interchangeable? Many would say that the question, "What is the difference between education and schooling?" if not actually improper, involves a verbal quibble and to that extent deserves to be dismissed as a non-problem. English usage is essentially flexible in these matters, after all, not given to the terminological exactitude of other European languages.